Empirical Research through Ubiquitous Data Collection. - Henze, Niels; Shrazi, Alireza Sahami; Schmidt, Albrecht; Pielot, Martin; Michahelles, Florian (Computer (00189162), 2013)
Ubiquitous computing technologies enable new in situ data-collection opportunities that can reveal insights into mobile users' behaviors and preferences.